A truly feminine literature: Ana de Castro Osorio and the germination of feminist thought in Portugal in the 19th century - Valentim, Jorge Vicente [UNESP] (Univ Estado Rio Janeiro, 2017)
The present essay aims to reflect on the intellectual performance of the writer Ana de Castro Osorio (1872-1935) in the dissemination of a female literature in Portugal, beginning in the late nineteenth and early twentieth centuries, taking into account not only its dramatic and literary production for childhood, but, above all, its public interventions in the form of lectures and conferences. According to the aspects of feminist scenes in the late nineteenth century context, as pointed out by Genevieve Fraisse and Michelle Perrot (1994) and Anne-Marie Kapelli (1994), we aimed to demonstrate how the Portuguese writer produced texts in harmony with many of these ideological and artistic elements, contributing it also for the consolidation of a truly feminine literature, as Ana de Castro Osorio herself referred to. In our perspective, positive results in this way of reading are perceptible in two texts of her, originally written as lectures and here used as corpus of analysis.
Keywords: Feminine literature; Feminist scenes; Nineteenth Century; Ana de Castro Osorio